Os significados da tensão rural – urbano entre jovens rurais: identificações e projetos de vida - Farias, Adeline Araújo Carneiro (Universidade do Vale do Rio dos Sinos, 2016)
The present thesis shows the results of a survey that aimed to understand the meanings that the rural youth living in Roraima impose to the rural-urban tension, analyzing its interference in their identity process and life projects. Thus, we performed the techniques of focus groups and individual interviews with eighty-six rural youth who live in four different localities and arranged in extreme and central parts of the state of Roraima. Data were analyzed using the analysis technique of thematic content, considered as markers of differentiation two age groups of youths, sex, naturalness, the locality where they live and self-ethno racial identification. Were still considered aspects linked to the intense migratory process and the boundary location of the state of Roraima. We identified that the perceptions and meanings that the rural youth impose to the urban and rural areas impact on their identity processes considering that such construction works through contingency and differentiation. Thus, these meanings also influence on their conflicts about the life projects.
Keywords: Juventudes; Identidades; Tensão rural-urbano; Hibridismo cultural; Projetos de vida; Youths; Identities; Rural-urban tension; Cultural hybridity; Life projects; ACCNPQ::Ciências Humanas::Sociologia